Kindlin‐2 interacts with α‐actinin‐2 and β1 integrin to maintain the integrity of the Z‐disc in cardiac muscles. Issue 16 (2nd July 2015) - Qi, Lihua; Yu, Yu; Chi, Xiaochun; Xu, Weizhi; Lu, Danyu; Song, Yao; Zhang, Youyi; Zhang, Hongquan
Abstract : Kindlin‐2, as an integrin‐interacting protein, was known to be required for the maintenance of cardiac structure and function in zebrafish. However, the mechanism remains unclear. We found that Kindlin‐2 interacts and colocalizes with α‐actinin‐2 at the Z‐disc of mouse cardiac muscles and there Kindlin‐2 also interacts with β1 integrin. Knockdown of Kindlin‐2 influences the association of β1 integrin with α‐actinin‐2 and disrupts the structure of the Z‐disc and leads to cardiac dysfunction. Our data indicated that Kindlin‐2 is a novel α‐actinin‐2‐interacting protein and plays an important role in the regulation of cardiac structure and function. Abstract : Kindlin‐2 colocalizes with α‐actinin‐2 at the Z‐disc. Kindlin‐2 interacts with α‐actinin‐2 and integrin β1. Knockdown of Kindlin‐2 disrupts the Z‐disc structure. Knockdown of Kindlin‐2 affects cardiac systolic function.